Hybrid Repair of Type B Aortic Dissection With Thoracoabdominal Aortic Aneurysmal Degeneration in the Setting of Marfan Syndrome. (August 2021) - Aru, Roberto G.; Richie, Cheryl D.; Badia, Daniel J.; Romesberg, Amanda M.; Sheppard, Mary B.; Minion, David J.; Tyagi, Sam
Aneurysmal degeneration of the thoracoabdominal aorta after aortic dissection is a well-documented sequela of Marfan syndrome (MFS). Hybrid technique (HT), an emerging treatment modality for complex aortic pathologies, decreases morbidity and mortality relative to open surgery. However, outcome data regarding HT in genetic aortopathies such as MFS is limited. We describe a case of a young male with hypertension and type B aortic dissection (AD) complicated by a symptomatic thoracoabdominal aortic aneurysm (TAAA). He underwent staged HT comprised of carotid-carotid transposition followed by zone 1 thoracic endovascular aortic repair and concurrent retrograde left subclavian stent graft placement. Genetic analysis was consistent with Marfan syndrome. Subsequent growth of his TAAA warranted open extent type IV TAAA repair with individual renovisceral and iliac bypasses. The patient recovered from the second surgery without further progression of disease or late complication.